2016
DOI: 10.1002/adma.201504785
|View full text |Cite
|
Sign up to set email alerts
|

Trimetallic TriStar Nanostructures: Tuning Electronic and Surface Structures for Enhanced Electrocatalytic Hydrogen Evolution

Abstract: PtFeCo alloy nanostructures in a TriStar shape with tunable Fe and Co content are developed for the electrocatalytic hydrogen evolution reaction (HER). With electronic and surface structures well-tailored, the PtFeCo nanostructures exhibit dramatically enhanced performance in HER against commercial Pt/C and other Pt-based nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
122
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(126 citation statements)
references
References 46 publications
3
122
1
Order By: Relevance
“…Platinum, as ‘the Holy Grail’ of HER electrocatalysts, remains the best HER catalysts with nearly zero overpotential and excellent long-term durability3111213. Unfortunately, the widespread commercialization of Pt-based electrocatalysts are hindered by their scarcity and expensive price1415.…”
mentioning
confidence: 99%
“…Platinum, as ‘the Holy Grail’ of HER electrocatalysts, remains the best HER catalysts with nearly zero overpotential and excellent long-term durability3111213. Unfortunately, the widespread commercialization of Pt-based electrocatalysts are hindered by their scarcity and expensive price1415.…”
mentioning
confidence: 99%
“…Combined with the polarization curves analyzed above, we may safely draw the conclusion that the 3D porous structure not only contributes to the charge transfer but can also produce an enlarged active area and thus contribute favorably to the final hydrogen evolution. These results also reveal that MoCN-3D is among the most active nonprecious HER electrocatalysts in acidic solutions [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][32][33][34][35][36][37][38] (Supplementary Tables S3 and S4). …”
Section: Catalytic Performancementioning
confidence: 68%
“…4 In recent years, a wide variety of transition metals (Co, Ni, Fe, Mo and W) and derivative components have been selected as effective candidates. [5][6][7][8][9][10][11] Particularly, β-phase molybdenum carbides have been demonstrated as highly active HER catalysts, even though they are bulky particles, and their performances could be further improved by constructing proper nanostructures. [12][13][14][15][16][17] It was revealed that nanorods of β-Mo 2 C work better as an electrocatalyst for HER than bulk β-Mo 2 C. 12 In addition to the morphology contribution, hybridization with heteroatom-doped graphitic carbon could further improve its performance because the effective coupling between β-Mo 2 C and N-doped graphitic carbon can greatly modify the work function of the hybrid and thus reduce the proton adsorption and the reaction barrier.…”
Section: Introductionmentioning
confidence: 99%
“…The tunable Tafel slopes observed in our work indicate that the HER occurring at the S sites has been altered by the addition of Pd components [18]. During the process, the bond formation and cleavage of the site-H should have a strong correlation with the electron density of the active sites [19,20]. We thus focus on the interface of Pd with MoS 2 and hypothesize that the difference in work functions (5.12 eV for Pd versus 6.53 eV for MoS 2 ) will induce the accumulation of negative charges on MoS 2 through charge polarization at the Pd-MoS 2 interface [21,22].…”
Section: Resultsmentioning
confidence: 67%